Challenges and perceptions of cancer patients attending a tertiary care center during COVID 19 Pandemic Era: Patient’s Perspective - Gupta, Yashna; Pandey, Laxman; Garg, Pankaj Kumar; Sehrawat, Amit; Gupta, Sweety; Joseph, Deepa; Abraham, Bruzily; Pasricha, Rajesh; Gupta, Manoj (Asian Journal of Medical Sciences, 2020)
Background: Patients with cancer are more susceptible to acquire SARS-Cov-2 infection due to their immunocompromised state related to the disease and anticancer treatment. There is a lack of literature assessing the patient’s perspective of the present crisis and its impact on their treatment. Aims and Objective: The present study aimed to address the challenges and sufferings faced by patients with cancer during their treatment in the current COVID-19 pandemic era. Materials and Methods: A single-institute, cross-sectional questionnaire-based observational study was conducted in a tertiary care teaching hospital. Patients attending the Oncology outpatient department were enrolled in the study. Results: One hundred patients (64 males, 36 females) with a mean age of 47.17 years (range-24-71) participated in the study. The majority of patients (89%) were aware of the COVID 19 symptoms and did not confuse them with cancer symptoms. Most of them were aware of preventive measures like frequent hand washing, sanitizer usage, and face masks to reduce the risk of infection. Almost half of them encountered difficulties in commuting to the Hospital. Most (83%) of them were worried about treatment delay and disease progression due to the COVID-19 pandemic. Almost half of the patients (54%) were fearful of acquiring the infection from the radiotherapy machine and immobilizing devices. Two-third of the patients (64%) were afraid to carry the virus back to their homes. Awareness regarding our Hospital’s teleconsultation facility was limited among patients. Conclusion: The present study underscores the success of ongoing COVID-19 awareness programs run by the government. However, there is an urgent need to address the various challenges encountered by patients with cancer. The strengthening of telemedicine facilities may reduce the in-person visits made by the patients.